2022
DOI: 10.3389/fnins.2021.795553
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Algorithm Trained on Brain Magnetic Resonance Images and Clinical Data to Predict Motor Outcomes of Patients With Corona Radiata Infarct

Abstract: The early and accurate prediction of the extent of long-term motor recovery is important for establishing specific rehabilitation strategies for stroke patients. Using clinical parameters and brain magnetic resonance images as inputs, we developed a deep learning algorithm to increase the prediction accuracy of long-term motor outcomes in patients with corona radiata (CR) infarct. Using brain magnetic resonance images and clinical data obtained soon after CR infarct, we developed an integrated algorithm to pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Compared with these traditional methods for counting vertebra number, our recently developed deep learning model showed high accuracy (93.3%) for detecting the L5 vertebra on anteroposterior lumbar spine radiographs. Deep learning models are characterized by multilayer structures with multiple hidden layers; they thus have a better detection accuracy ability than traditional shallow learning models [8]. We therefore believe that our deep learning model extracts valuable features that differentiate the L5 vertebra from other vertebral levels.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Compared with these traditional methods for counting vertebra number, our recently developed deep learning model showed high accuracy (93.3%) for detecting the L5 vertebra on anteroposterior lumbar spine radiographs. Deep learning models are characterized by multilayer structures with multiple hidden layers; they thus have a better detection accuracy ability than traditional shallow learning models [8]. We therefore believe that our deep learning model extracts valuable features that differentiate the L5 vertebra from other vertebral levels.…”
Section: Discussionmentioning
confidence: 98%
“…Deep learning techniques have recently emerged as powerful methods to automatically learn feature representations from data. [8][9][10] In particular, these techniques can substantially improve object detection. 11 Object detection refers to determining whether there are any instances of objects from specified categories in an image; if there are, the spatial location and extent of each object instance are shown via a bounding box.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a regression model that used both low- and high-order functional connectivity predicted the results based on the correlation coefficient (r = 0.54, p = 0.0002). In 2022, Kim et al [ 47 ] used clinical data, including age, sex, modified Brunnstrom classification, functional ambulation score, and Medical Research Council score at an early stage (8–30 days following stroke onset), and MR image data (three images from each patient) of the same 221 corona radiata infarct patients as input to develop the prediction model. This study demonstrated that an integrated algorithm trained using clinical data of patients and brain MR images could improve the accuracy of the prediction of long-term upper extremity function and ambulatory outcomes.…”
Section: Machine Learning Algorithms Trained On Image Datamentioning
confidence: 99%
“…This study demonstrated that the use of deep learning models can accurately predict long-term outcomes and record a significantly higher AUC than the ASTRAL score [ 108 ]. Kim et al developed an integrated modified Brunnstrom algorithm to predict the hand function and the ambulatory outcomes of a patient with corona radiata (CR) at 6 months after onset, using clinical parameters and brain magnetic resonance images as input, with an AUC of 0.891 [ 109 ]. Ding et al employed CNNs to predict the functional outcomes at 3 months poststroke with acute brainstem infarction using clinical features, laboratory features, conventional imaging features (infarct volume and number of infarctions), and DWI neuroimaging features from 1482 patients, which achieved an extremely high AUC of 0.975 [ 110 ].…”
Section: Clinical Applications Of Deep Learning In Aismentioning
confidence: 99%